Hund’s metal regimes and orbital selective Mott transitions in three band systems - Facio, Jorge Ismael; Cornaglia de la Cruz, Pablo Sebastian (IOP Publishing, 2019)
Fil: Facio, Jorge Ismael. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Institute for Theoretical Solid State Physics; Alemania